A Bayesian look at new open economy - Thomas Lubik; Frank Schorfheide (The Johns Hopkins University, Department of Economics, 2005)
This paper develops a small-scale two country model following the New Open Economy Macroecoenomics paradigm. Under autarky the model specializes to the familiar three equation New Keynesian dynamic stochastic general equilibrium (DSGE) model. We discuss two challenges to successful estimation of DSGE models: potential model misspecification and identification problems. We argue that prior distributions and Bayesian estimation techniques are useful to cope with these challenges. We apply these techniques to the two-country model and fit it to data from the U.S. and the Euro Area. We compare parameter estimates from closed and open economy specifications, study the sensitivity of parameter estimates to the choice of prior distribution, examine the propagation of monetary policy shocks, and assess the model's ability to explain exchange rate movements.
Keywords: 330; Zwei-Länder-Modell; Dynamisches Gleichgewicht; Neukeynesianische Makroökonomik; Bayes-Statistik; Schätzung; USA; EU-Staaten; Neue Makroökonomik offener Volkswirtschaften